Modified ridge splitting and bone expansion osteotomy for placement of dental implant in esthetic zone - Mayur S Khairnar; Darshana Khairnar; Kedar Bakshi (Wolters Kluwer Medknow Publications, 2014)
Ridge splitting with bone expansion is a technique of manipulation of bone to form receptor site for implant without removing any bone from the implant site. Maxillary bone has inherent quality of flexibility which can bemolded to desire location by using series of instrument namely chisels and osteotome. This further improves quality of bone all around implant, at the crest and apex both. This article describes a report of a clinical case with management of bucco-palatal ridge defect with modified ridge splitting and expansion osteotomy technique using chisel and osteotomes in an esthetic zone.